Educational spaces and its community relationship in Quebrada Verde Pachacamac, Lima, Peru: an analysis about quality (REVISTA NODO, 2022)
In this article, basic standards of quality for didactic spaces are ordered, all of which are developed based on national and international guides and manuals. These standards will be useful to develop contemporary educational spaces that could relate to the natural environment of their surroundings. In this case, the Santa María Reyna school of Quebrada Verde in Pachacamac, Lima, Peru, is analyzed around the variables of educational furniture, spatial flexibility, materiality and efficiency- comfort, as well as the school’s relationship with the Lúcumo Hills ecosystem where it is located. The methodology of this research is descriptive, analytical and correlational; the instrument in development is the observation guide. The conclusion is that the educational spaces of the study center are not of high quality, which causes delays in the progress of the activities carried out by their users.
Keywords: educational architecture; classrooms; quality; efficiency and comfort; natural environments; educational spaces